Hajj Abdul Hussein jita (1911-1969) (Historcal study) - Hisham Khammas, Assist. Lect . Rafal (Basra studies journal, 2025)
The religious and social diversity in Basra during the twentieth century allowed for the emergence of prominent figures such as Hajj Jita، whose identity combined a foreign background with an authentic Iraqi–Basri character. He contributed sincerely to the building of society، demonstrating that national wealth، when bound by religious and ethical values، can become a powerful instrument for development and public service. This was embodied in his numerous projects، which often preceded the state’s own institutions in areas such as education، healthcare، and social welfare. Hajj Jina exemplified the principle that charitable work is not a sin even when met with suspicion by adversaries or exploited by oppressive systems seeking to undermine their benefactors. His experience presents a recurring lesson in history: genuine patriotism and devotion، even when operating under fragile or hostile conditions، can still leave an enduring legacy. Ultimately، his martyrdom transformed him into an eternal symbol embedded in the memory of Basrans and Iraqis alike، remembered for his steadfast commitment to truth، principle، and altruism without expectation of return.